Melatonin Increases the Chilling Tolerance of Chloroplast in Cucumber Seedlings by Regulating Photosynthetic Electron Flux and the Ascorbate-Glutathione Cycle - Zhao, Hailiang; Ye, Lin; Wang, Yuping; Zhou, Xiaoting; Yang, Junwei; Wang, Jiawei; Cao, Kai; Zou, Zhirong (Frontiers in Plant Science, 2016)
The aim of the study was to monitor the effects of exogenous melatonin on cucumber (Cucumis sativus L.) chloroplasts and explore the mechanisms through which it mitigates chilling stress. Under chilling stress, chloroplast structure was seriously damaged as a result of over-accumulation of reactive oxygen species (ROS), as evidenced by the high levels of superoxide anion (O2-) and hydrogen peroxide (H2O2). However, pretreatment with 200 μM melatonin effectively mitigated this by suppressing the levels of ROS in chloroplasts. On the one hand, melatonin enhanced the scavenging ability of ROS by stimulating the ascorbate–glutathione (AsA-GSH) cycle in chloroplasts. The application of melatonin led to high levels of AsA and GSH, and increased the activity of total superoxide dismutase (SOD, EC 1.15.1.1), ascorbate peroxidase (APX, EC 1.11.1.11), monodehydroascorbate reductase (MDHAR, EC 1.6.5.4) dehydroascorbate reductase (DHAR, EC 1.5.5.1), glutathione reductase (GR, EC1.6.4.2) in the AsA-GSH cycle. On the other hand, melatonin lessened the production of ROS in chloroplasts by balancing the distribution of photosynthetic electron flux. Melatonin helped maintain a high level of electron flux in the PCR cycle [Je(PCR)] and in the PCO cycle [Je(PCO)], and suppressed the O2-dependent alternative electron flux Ja(O2-dependent) which is one important ROS source. Results indicate that melatonin increased the chilling tolerance of chloroplast in cucumber seedlings by accelerating the AsA-GSH cycle to enhance ROS scavenging ability and by balancing the distribution of photosynthetic electron flux so as to suppress ROS production.